Impacts of urbanization and real economic development on CO2emissions in non-high income countries: Empirical research based on the extended STIRPAT model - Lin, S.; Wang, S.; Marinova, Dora; Zhao, D.; Hong, J. (Elsevier, 2017)
Â© 2017 Elsevier Ltd This article focuses on the effects of urbanization and economic development on carbon dioxide (CO 2 ) emissions in non-high income countries using the extended STIRPAT model. Following the building idea of the IPAT model, CO 2 emissions (I) are decomposed into nine factors: population, affluence, technology level, urbanization level, urban employment level, industrialization level, po pulation carrying intensity of the real economy built on goods and services, CO 2 emission intensity and energy intensity. Then the extended IPAT model is reconstructed as the extended STIRPAT model. Furthermore, based on panel data from 1991 to 2013 and using the extended STIRPAT model, this article respectively analyzes the effects of the driving forces, especially urbanization and real economic development, on CO 2 emissions for non-high income countries, upper and lower middle-income countries. The results indicate that urbanization and real economic development have a small impact on CO 2 emissions in non-high income countries. Accelerating urbanization and real economic development will not result in a significant increase in CO 2 emissions. In fact, for upper middle-income countries, real economic development will lead to a decrease in CO 2 emissions, and acceleration of the urbanization process will only cause a small increase in emissions. The main driving factors of CO 2 emissions remain population, affluence, energy intensity and CO 2 emission intensity. This article also quantitatively calculates the actual contribution rate of each driving force for the 1991â€“2013 period. The study contributes to understanding the emission characteristics and key driving forces in each type of countries, allowing for appropriate policy recommendations.